Development and Properties of Polymeric Nanocomposite Coatings - Muddasir Nawaz (17052438) (2019)
Polymeric-based nanocomposite coatings were synthesized by reinforcing epoxy matrix with titanium nanotubes (TNTs) loaded with dodecylamine (DOC). The performance of the developed nanocomposite coatings was investigated in corrosive environments to evaluate their anti-corrosion properties. The SEM/TEM, TGA, and FTIR analysis confirm the loading of the DOC into the TNTs. The UV-Vis spectroscopic analysis confirms the self-release of the inhibitor (DOC) in response to the pH change. The electrochemical impedance spectroscopic (EIS) analysis indicates that the synthesized nanocomposite coatings demonstrate superior anticorrosion properties at pH 2 as compared to pH 5. The improved anticorrosion properties of nanocomposite coatings at pH 2 can be attributed to the more effective release of the DOC from the nanocontainers. The superior performance makes polymeric nanocomposite coatings suitable for many industrial applications. Other Information Published in: Polymers License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/polym11050852